Clinical phenotypes of COPD and health-related quality of life: a cross-sectional study - Chai CS (International Journal of COPD, 2019)
Chee-Shee Chai,1 Chong-Kin Liam,2 Yong-Kek Pang,2 Diana Leh-Ching Ng,1 Seng-Beng Tan,2 Tat-Seng Wong,2 Jo-Ee Sia2 1Department of Medicine, Faculty of Medicine and Health Science, Universiti Malaysia Sarawak, Kota Samarahan, Malaysia; 2Department of Medicine, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia Introduction: The Spanish COPD guideline (GesEPOC) classifies COPD into four clinical phenotypes based on the exacerbation frequency and dominant clinical manifestations. In this study, we compared the disease-specific health-related quality of life (HRQoL) of patients with different clinical phenotypes. Methods: This was a cross-sectional study of patients with COPD attending the respiratory medicine clinic of University of Malaya Medical Centre from 1 June 2017 to 31 May 2018. Disease-specific HRQoL was assessed by using the COPD Assessment Test (CAT) and St George’s Respiratory Questionnaire for COPD (SGRQ-c). Results: Of 189 patients, 28.6% were of non-exacerbator phenotype (NON-AE), 18.5% were of exacerbator with emphysema phenotype (AE NON-CB), 39.7% were of exacerbator with chronic bronchitis phenotype (AE CB), and 13.2% had asthma-COPD overlap syndrome phenotype (ACOS). The total CAT and SGRQ-c scores were significantly different between the clinical phenotypes (P<0.001). Patients who were AE CB had significantly higher total CAT score than those with ACOS (P=0.033), AE NON-CB (P=0.001), and NON-AE (P<0.001). Concerning SGRQ-c, patients who were AE CB also had a significantly higher total score than those with AE NON-CB (P=0.001) and NON-AE (P<0.001). However, the total SGRQ-c score of AE CB patients was only marginally higher than those who had ACOS (P=0.187). There was a significant difference in the score of each CAT item (except CAT 7) and SGRQ-c components between clinical phenotypes, with AE CB patients recording the highest score in each of them. Conclusion: Patients who were AE CB had significantly poorer HRQoL than other clinical phenotypes and recorded the worst score in each of the CAT items and SGRQ-c components. Therefore, AE CB patients may warrant a different treatment approach that focuses on the exacerbation and chronic bronchitis components. Keywords: chronic obstructive pulmonary disease, chronic bronchitis, asthma, clinical phenotypes, health-related quality of life, emphysema, exacerbation